THE RELATIONSHIP OF APRI SCORE (ASPARTATE AMINOTRANS FERASE-TO-PLATELET RATIO INDEX) AND PUGH CHILD SCORE - Adelia Muhlifa Saputri; Magdaleni Agustina Rahayu; Sinta Murti (Universitas Muhammadiyah Kalimantan Timur, 2019)
Liver cirrhosis is the last stage of chronic liver disease that is in the path of the disease can cause damage of liver function and/or portal hypertension. The prognosis of liver cirrhosis can be assessed by manifestations of liver function disorders with Child Pugh score that include the presence or absence of ascites, encephalopathy, bilirubin serum, albumin serum, and prothrombin time or INR, while portal hypertension also occurs in patient of cirrhosis can lead the formation of esophageal varices. APRI score has platelet count and AST serum as its variable is suspected to be related to the Child Pugh score in assessing prognosis of cirrhosis patients. This study purposed to find the relation between APRI score (Aspartate Aminotransferase-to-Platelet Ratio Index) and Child Pugh score. Purpose of this research is to find the relation between APRI score (Aspartate Aminotransferase-to-Platelet Ratio Index) and Child Pugh score and degree of esophageal varices in patients with cirrhosis. Method used is a retrospective analytic study with cross sectional approach. The data source is secondary source. The sample in this study were patients with liver cirrhosis who were diagnosed by a doctor and had complied the inclusion criteria. The data obtained was analyzed using ANOVA. The result of this study is include 48 cirrhosis patients, male 81,3%, with a mean age 49,98 years. The most common cause of cirrhosis is hepatitis B obtained from reactive HBsAg examination in 33 patients (68,8%). The APRI score was found to have a weak correlation (r = 0.044) and not significant (p = 0.868) with the Child Pugh score. The APRI score do not able to assess the prognosis in advanced cirrhotic patients.